Effect of Zn Content on Microstructure and Corrosion Resistance of 7010 Aluminum Alloy Used for Vehicle Lightweight - LI Yan-fen, CHENG Cai-xia, YANG Tie-zao (Cailiao Baohu)
In order to improve the corrosion resistance of 7010 aluminum alloy for vehicle lightweight, 7010 alloy was modified by adding Zn with different dosage.After modification, the microstructure of modified alloy was analyzed by SEM and EDS, and the corrosion resistance were evaluated by immersion test in NaCl + HNO3 +KNO3 corrosive medium.Results showed that the second phase particles in the alloy structure showed ellipsoidal shape and belonged to AlZnMgCu phase.The increase of Zn addition caused more significant alloying processes occurred, which formed more residual second phase in the matrix, and the grain boundary precipitated phase possessed more continuous distribution and smaller size.When the Zn content increased, a higher content of Zn and Mg was produced in the precipitation phase at the grain boundary of each alloy.After corrosion medium immersing test, numerous corrosion pits with small size were generated on the surface of the sample, and many exfoliating layers with large size appeared in the surface area of the alloy with 10% Zn content, performing very serious corrosion.When the Zn content increased from 6% to 10%, the corrosion resistance of the alloy decreased gradually.